Ensnarement of prisoners' families to poverty and crime in South Africa: a case of Polokwane Medium B Prison - Khwela, Michael Nkosinathi (My University, 2015)
The purpose of this study was to assess the poverty and crime levels among the offenders’ families and to compare the perceptions of the offenders and correctional officials regarding incarceration and rehabilitation in the correctional centres with the view of developing an adjusted framework for the Department of Justice and Correctional Services. The study utilised a mixed method approach and was descriptive. The study used survey method to collect quantitative and qualitative data. Quantitative data were collected using self-administered structured questionnaires and qualitative data used self-administered semi-structured questionnaires and open-ended questions. Three groups of respondents participated in this study. The population for the quantitative design were offenders (n=59) and correctional officials (n=17), respectively from Polokwane Medium B Prison. Participants for the qualitative design were the same correctional officials (n=17) and offenders’ families (n=10). Quantitative data was analysed using SPSS version 22 package while qualitative data was coded and analysed manually. The majority of offenders (66%) indicated that their families were struggling while they were incarcerated and corroborated by 59% of the correctional officials, whereas 80% of the offenders’ families were evidenced during the interview that they were struggling. The findings revealed that incarceration and rehabilitation lead to recidivism and the ensnarement of offenders’ families to poverty and crime. The study revealed that overcrowding, limited staff and lack of staff with expertise were the contributing factors to the ineffectiveness of rehabilitation programmes in the correctional centre. The study recommends the coordinated efforts of the stakeholders (government departments and NGOs) for improving the implementation of the remunerated work for the offenders. The researcher is optimistic that if the proposed adjusted incarceration and rehabilitation framework is implemented, the poverty among the offenders’ families might be alleviated. KEY CONCEPTS: incarceration; rehabilitation; recidivism; offenders’ families; prisoners; correctional officials; mixed research methodology.
Thesis (Ph. D. (Administration)) -- University of Limpopo, 2016
Keywords: Incarceration; Offenders’ families; Prisoners' families; Poverty; Crime